10-21-92 Sand Volleyball Tournament - Becky Rouse; Linn-Benton Community College (2018)
Image 45 was mirrored and used in Volume 24, Edition 3: http://libarchive.linnbenton.edu/concern/newspaper_issues/7s75dc47g?locale=en